34 MALARIA: A VISITOR FROM THE TROPICS. Issue 1 (1st January 2007) - Atwal, P.; Rehman, M.; Atwal, C.; Taj, M.; Niranjan, S.
Abstract : Malaria is a parasitic infection that is transmitted through the bite of an infected Anopheles mosquito. Four species of the genus Plasmodium are responsible for human malaria: P. vivax, P. malariae, P. ovale, and P. falciparum . Typical malarial attacks show sequentially over 4 to 6 hours: shaking chills (cold stage), fever (hot stage), and marked diaphoresis (sweating stage). Associated symptoms may include fatigue, headache, dizziness, and gastrointestinal symptoms. The thick and thin blood film, dehemoglobinized and Giemsa stained or Wright stained, is the mainstay of diagnosis. Many drug regimens are available for treatment. Knowledge of the geographic area where the infection was acquired provides information on the likelihood of drug resistance of the infected parasite and enables the physician to choose an appropriate drug regimen. A 35-year-old African male with a history of recent travel to Chad (Africa) presented with fever, chills, headache, fatigue, and malaise. Physical examination revealed no significant abnormalities. Peripheral thick and thin blood smears showed intraerythrocytic P. falciparum parasites with 3.5% parasitemia. The patient was successfully treated with oral doxycycline and quinine sulfate, as demonstrated by clinical improvement. Although the disease has been eradicated from most temperate zone countries, it continues to be endemic in many parts of the tropics and subtropics and imported cases occur in the United States. In a patient presenting with fever associated with suggestive symptoms and a history of recent travel to an endemic area, malaria must be considered as failure to treat can result in significant morbidity or mortality, especially in children, pregnant women, or immunocompromised patients.